2018
DOI: 10.20474/jahss-4.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the credibility of eword-of-mouth using customer reviews on social media

Abstract: Eword-of-mouth Credibility Word-of-mouth Social media

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The term credibility encompasses a variety of dimensions, such as the quality, currency, accuracy and meaningfulness of a shared message, the credibility of the message producer and the reliability of the medium through which the message is communicated (Afify et al, 2019;Aladhadh et al, 2019;Metzger and Flanagin, 2013;Li and Suh, 2015;Xiao et al, 2018). Previously, many research studies have empirically demonstrated the impact of IC on social media IAB and concluded that IC is the key factor in online information adoption (Albon et al, 2018;Assaker, 2020;Chiou et al, 2018;Elwalda et al, 2021;Erkan and Evans, 2016;Hajli, 2018; Impact of IC on social media IAB Ismagilova et al, 2020;Makki et al, 2018;Xie et al, 2020). While investigating the impact of electronic word of mouth (eWOM), Khoa and Khanh (2020) supported the argument that the credibility of information has a direct impact on information adoption, furthermore, the investigators found that recipients feel no hesitation to adopt received information if they assured that the information came from an authentic source.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The term credibility encompasses a variety of dimensions, such as the quality, currency, accuracy and meaningfulness of a shared message, the credibility of the message producer and the reliability of the medium through which the message is communicated (Afify et al, 2019;Aladhadh et al, 2019;Metzger and Flanagin, 2013;Li and Suh, 2015;Xiao et al, 2018). Previously, many research studies have empirically demonstrated the impact of IC on social media IAB and concluded that IC is the key factor in online information adoption (Albon et al, 2018;Assaker, 2020;Chiou et al, 2018;Elwalda et al, 2021;Erkan and Evans, 2016;Hajli, 2018; Impact of IC on social media IAB Ismagilova et al, 2020;Makki et al, 2018;Xie et al, 2020). While investigating the impact of electronic word of mouth (eWOM), Khoa and Khanh (2020) supported the argument that the credibility of information has a direct impact on information adoption, furthermore, the investigators found that recipients feel no hesitation to adopt received information if they assured that the information came from an authentic source.…”
Section: Discussionmentioning
confidence: 99%
“…, 2018). Previously, many research studies have empirically demonstrated the impact of IC on social media IAB and concluded that IC is the key factor in online information adoption (Albon et al. , 2018; Assaker, 2020; Chiou et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Showrooming behaviour occurs for some reasons, such as inadequate salesperson knowledge about the products, unsatisfactory service, and less competitive prices ( (Albon, Kraft, & Rennhak, 2018;Cooper, 2012;Zimmerman, 2012). If the salespersons can provide good service and information to customers, it will reduce the occurrence of showrooming behavior (Clancy, 2012;Cooper, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%